Energy distribution in RC shear wall-frame structures subject to repeated earthquakes - Jamnani, Hamed Hamidi; Amiri, Javad Vaseghi; Rajabnejad, Hamid (Soil dynamics and earthquake engineering (1984), 2018)
Repeated earthquakes are possible events in seismic zones. The aftershocks can grow so large that they can be regarded as design-level earthquakes. These can affect the nonlinear behavior of structures. Different studies indicated that the destructions caused by earthquakes were highly influenced by the seismic energy induced to the structure during the earthquake. This study investigated the seismic behavior of RC shear wall-frame structures and the structural response and energy distribution in these structures subject to single and sequence of natural records. To this end, 10-, 15-, and 20-story structures were assessed for the selected structural system. Previous studies assessed the displacement, maximum drift, maximum residual drift, and energy distribution in structures. Therefore, this research aimed to study the records of the repeated sequences and their energy concepts. The results of analyses revealed that repeated earthquakes led to increase in seismic requirements of RC shear wall-frame structure, but it did not cause structural collapse. In addition, the presence of the second record reduced the residual structural displacement in some cases. Nevertheless, the effect of repeated earthquakes should be taken into consideration in the assessment of the reliability of structures. Other results on energy distribution indicate that an increase in the structure height will possibly increase the contribution of α[M] and decrease the contribution of β[K] in dissipation of input energy. •Destructions caused by earthquakes are highly influenced by the seismic energy.•More realistic results can be expected by investigating the effect of repeated earthquakes on structures.•When the input energy in the structure is increased, this distribution is transferred to the lower stories of the structure.•An increase in the structure height will possibly increase the contribution of α[M] and decrease the contribution of β[K].